2012
DOI: 10.1161/circulationaha.112.095281
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Infective Endocarditis Caused by Viridans Group Streptococci Before and After Publication of the 2007 American Heart Association's Endocarditis Prevention Guidelines

Abstract: Background The American Heart Association (AHA) published updated guidelines for infective endocarditis (IE) prevention in 2007 that markedly restricted the use of antibiotic prophylaxis in certain at-risk patients undergoing dental and other invasive procedures. The incidence of IE due to viridans group streptococci (VGS) in the United States following publication of the 2007 AHA guidelines has not been reported. Methods and Results We performed a population-based review of all definite or possible cases of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
62
0
7

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(76 citation statements)
references
References 20 publications
7
62
0
7
Order By: Relevance
“…Na podstawie wyników 2 badań przeprowadzonych w Stanach Zjednoczonych nie wykazano negatywnego wpływu zaniechania profilaktyki antybiotykowej u pacjentów z chorobami własnych zastawek po opublikowaniu wytycznych Amerykańskiego Towarzystwa Kardiologicznego (AHA) w 2007 r. [34,35]. W nowszych analizach danych z baz administracyjnych zanotowano wzrost częstości hospitalizacji z powodu IZW w latach 2000-2011, ale bez istotnych zmian po wprowadzeniu amerykańskich wytycznych w 2007 r. [36].…”
Section: Podstawyunclassified
See 1 more Smart Citation
“…Na podstawie wyników 2 badań przeprowadzonych w Stanach Zjednoczonych nie wykazano negatywnego wpływu zaniechania profilaktyki antybiotykowej u pacjentów z chorobami własnych zastawek po opublikowaniu wytycznych Amerykańskiego Towarzystwa Kardiologicznego (AHA) w 2007 r. [34,35]. W nowszych analizach danych z baz administracyjnych zanotowano wzrost częstości hospitalizacji z powodu IZW w latach 2000-2011, ale bez istotnych zmian po wprowadzeniu amerykańskich wytycznych w 2007 r. [36].…”
Section: Podstawyunclassified
“…Chociaż powyższy rozdział wytycznych dotyczą-cy profilaktyki IZW opiera się na dowodach o niż-szym poziomie wiarygodności, zostały one ostatnio wzmocnione wynikami badań epidemiologicznych, w większości których nie wykazano zwiększonej częstości występowania IZW spowodowanego przez paciorkowce jamy ustnej [33][34][35]. Zastosowanie opisywanych metod profilaktyki przez pacjentów powinno nastąpić w wyniku wspólnego procesu decyzyjnego.…”
Section: Interwencje Sercowo-naczynioweunclassified
“…Two retrospective studies in the USA 27,28 showed no changes in the rate of infective endocarditis due to viridans streptococci three years after the revision of the guidelines in 2007. A third study found a significant increase in streptococcal infective endocarditis, but it Antibiotic prophylaxis for dental procedures…”
Section: Outcome Studiesmentioning
confidence: 99%
“…Macrolides have little activity against periodontal pathogens, and in recent years their activity against streptococcal species has declined to such a degree that most experts discourage their use in odontogenic infections as well. Desimone et al 9 analyzed 150 cases of infective endocarditis in Olmstead County, Minnesota, that occurred from 1999 through 2010. Of 22 cases attributable to viridans group streptococci,~95% were sensitive to penicillin but only~71% to macrolides.…”
Section: Macrolidesmentioning
confidence: 99%
“…As mentioned previously, resistance to macrolides is increasing and any recommendation for their use may be modified in future guidelines. 9 In some cases, a patient may present for treatment having not premedicated. The following is a direct quote from the current American Heart Association guidelines; simply stated, administer the antibiotic regimen and complete the treatment!…”
Section: Medical Prophylaxismentioning
confidence: 99%